A reinvenção da escola : história, memórias e práticas educativas no período colonizatório de Sinop – MT (1973-1979) - Rohden, Josiane Brolo (2012)
This research has as object of study the school culture produced by the Nilza de Oliveira Pipino State School, located in Sinop, Mato Grosso, locus of this research, elected as an object of study for being the first school established at this location during the colonization process of the city. It represents the beginning of an educational system in an Amazon rainforest wilderness and therefore more than fulfill their educational functions, this school and education generally represented in that historical context, a fundamental instrument for the construction of a city dedicated to the establishment of migrants. Take as a point of reference in this investigation, the years from 1973 to 1979. The choice and delimitation of chronological cut-off is due to the fact that education, as well as the city of Sinop were instituted in the year 1973 and, at the end of the same decade, in 1979, would the political emancipation of the city and with it significant changes in the socio-political scene of the city. In the colonization movement, thousands of people left their homeland, mainly from the southern region of the country, to occupy the space under study. In this way, do an inventory of school practices, values, and standards of conduct to be followed, the content to be taught is an interesting work because it allows, in addition to understand the daily life of school space, also discuss the traditions, the customs brought by migrants and that would be maintained and passed on by the school, besides enabling a discussion re-meaning the story of the first institution. One of the goals of the research, emphasizes the need to understand how it was organized the first school's education system during the period enclosed and that there should be taught, discussing their values and standards needed to ensure the process of schooling, inferring on the customs, practices, cultural traditions maintained and passed on by the school, in particular, it is intended to highlight the arts of making mainly from Michel de Certeau conceptions, since the initiative of the ' construction ' of the school by the migrants, but also as regards the creative, inventive and astute dynamic, of those who participated in their daily lives in the school. For the construction and development of research, it was appropriated school documents, schedules of students and teachers, class diaries and photographs which were acquired not only in school, but also in private and public collections. Still in the context of Oral History interviews were conducted with former professors and students to ' hear ' the voices of those who have not had their recorded history. This research suggests discussing how the school is configured as a place of production of a particular culture, in that they are often created shaping strategies and tactics of subversion, and how power relations are revealed within the educational institutions, as an area in which determine social relationships, while at the same time constitutes as broadcast knowledge.